First record of the red gum lerp psyllid Glycaspis brimblecombei Moore (Hemiptera: Psyllidae) in Tuscany (Italy). (18th April 2013) - Frasconi, C.; Rossi, E.; Antonelli, R.; Loni, A.
<x xml:space="preserve">Abstract</x> The invasive Australian pest Glycaspis brimblecombei Moore, the red gum lerp psyllid, is recorded for the first time in Tuscany (Italy). Its occurrence in this new region, just 2 years after its first record in Italy, shows how rapidly its population has found suitable environmental conditions in Italian territories.